Pemanfaatan Channel YouTube Adi Hidayat Official sebagai Media Penguatan Literasi Keagamaan dalam Pendidikan Agama Islam - Mayang Sari Lubis (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2026)
This study aims to analyze the utilization of the Adi Hidayat Official YouTube channel as a medium for strengthening religious literacy in Islamic Religious Education (PAI). Using a qualitative approach, the primary data were obtained through tracking and content analysis of the videos on the channel, while supporting data were sourced from relevant literature, journal articles, and previous research. The results of the study indicate that the content presented by Ustadz Adi Hidayat covers fundamental PAI material such as creed, morals, and worship, which is delivered systematically, logically, and based on classical references. The presentation of material, such as methods for memorizing the Qur’an, early childhood education through the story of the family of Imran, and habituating children to perform prayers, has been proven to contribute to the understanding and internalization of Islamic values among the audience. Content relevance analysis shows that the material presented aligns with the principles of Islamic Religious Education (PAI), reflects Qur'anic and Prophetic values, and emphasizes role modeling and digital ethics. Thus, the Adi Hidayat Official Channel plays a significant role as an Islamic learning medium that is adaptive to the needs of the digital generation and effective in strengthening the religious literacy of the community.